FACTORS AFFECTING THE QUALITY OF REGIONAL FINANCIAL SUPERVISION - Aspihani Ahyat; Sri Rahayu; Susfa Yetti (Management Department, Faculty of Economics and Business, Universitas Jambi, 2021)
This research was conducted to analyze several factors that affected the quality of the inspectorate supervision, namely Independence, objectivity, expertise, due professional care, and accountability. Multiple regression analysis was chosen for this research, and the F statistic test and T statistic test were utilized for Hypothesis Test. The result indicated that (1) independence affected the quality of the inspectorate supervision, (2) objectivity affected the quality of the inspectorate supervision, (3) expertise affected the quality of the inspectorate supervision, (4) due professional care did not affect the quality of the inspectorate supervision, (5) accountability affected the quality of the inspectorate supervision. The influence of Independence, objectivity, expertise, due professional care, and accountability toward the inspectorate supervision had a strong coefficient of determination.